1977
DOI: 10.1097/00000658-197702000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Intra-aortic Balloon Support in Surgery for Left Main Coronary Stenosis

Abstract: Twenty-six patients with left main coronary (LMC) stenosis were operated upon with preoperative intra aortic balloon pump (IABP) support. There was no mortality, and no morbidity attributable to the balloon catheter. The most delicate facet of revascularization surgery in this entity is the pre-cardiopulmonary bypass phase including anesthesia induction during which blood pressure fluctuation may further diminish severely compromised coronary flow. Although systolic pressure dropped to below 100 mm Hg in 50% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…17 , in a case series, reported that the prophylactic use of the balloon in revascularization surgery in the presence of left coronary trunk lesion was a safe strategy, with no increment of vascular complications. The surgical results were adequate and comparable to those obtained in lower risk surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…17 , in a case series, reported that the prophylactic use of the balloon in revascularization surgery in the presence of left coronary trunk lesion was a safe strategy, with no increment of vascular complications. The surgical results were adequate and comparable to those obtained in lower risk surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…14 If the patient is hemodynamically unstable or continues to have chest pain prior to urgent revascularization (either surgically or percutaneously), mechanical support (with an intra-aortic balloon pump or percutaneous left ventricular assist device) may be helpful in stabilizing the patient. [15][16][17] Placement of these devices requires additional time, so any foreknowledge that the patient might need them would be ideal. There are currently no clear advantages in the selection of the type of mechanical cardiac support device, but ongoing studies are looking at this question.…”
Section: Discussionmentioning
confidence: 99%
“…According to current guidelines, surgical revascularization with vascular graft is an absolute indication for patients with unprotected LMCA disease and PCI is an alternative when surgery is not manageable [31] [32]. During induction of anesthesia, and during operation before CPB, decrease in the oxygen supply-demand secondary to suddendrop of coronary blood flow which is not compensated by collateral circulation from RCA (because of RCA stenosis) may cause myocardial infarction [33]. Preoperative prophylactic usage of an IABP is still controversial in patients who have stable hemodynamic parameters but are at high risk [34].…”
Section: Discussionmentioning
confidence: 99%